Assessment of a Nonsteroidal Aromatase Inhibitor, Letrozole, in Juvenile Rats. (9th December 2013) - Pouliot, Louise; Schneider, Marilynn; DeCristofaro, Marc; Samadfam, Rana; Smith, Susan Y.; Beckman, David A.
<x xml:space="preserve">Abstract</x> BACKGROUND The timing and duration of letrozole administration was designed to encompass the majority of postnatal development in the rat with the intent of evaluating the potential for a broad range of effects but with emphasis on expected effects on skeletal maturation. METHODS Sprague‐Dawley rats were administered letrozole via oral gavage at doses of 0.003, 0.03, and 0.3 mg/kg/day beginning on postpartum day (PPD) 7 through 91 followed by a 6‐week recovery period. Clinical signs, body weight, food consumption, developmental endpoints, bone, ophthalmology, behavioral assessments, clinical/anatomic pathology, toxicokinetics, and reproductive assessments were conducted. RESULTS Growth (body weight gain and crown‐to‐rump length) and food consumption were increased in females at ≥0.03 mg/kg/day and decreased in males at ≥0.003 mg/kg/day. Delayed sexual maturation in both sexes and adverse effects on reproductive function occurred at all doses. Effects on bone growth and maturation were noted in both sexes at all doses. Evidence of recovery was noted for males at 0.003 mg/kg/day and females at 0.003 and 0.03 mg/kg/day upon withdrawal of treatment. Histopathological changes in the pituitary–adrenal–gonadal axis correlated with effects on reproductive function. CONCLUSIONS The observed effects in juvenile rats were considered predictable and primarily related to the mechanism of action of letrozole upon estrogen synthesis.